Re-examining the Rhetoric of Public Management Reform from a Critical Management Studies Perspective - Zaato, Joshua (Revue Gouvernance / Governance Review, 2009)
Public management reform is mostly presented as a rational, technical and objective process in public administration discourse. Driven by the neo-liberal ideological assault on the welfare state and influenced by the “private is better” mantra, it has been claimed, especially by NPM/Managerialism advocates, that there are superior ideas, concepts and models out there which are value free and have universal validity and application. It is also claimed that the adoption and implementation of these ideals can secure the goals of efficiency, efficacy and economy in public organization. Based on an analysis of the critical management literature however, this paper (1) explores the extent to which concepts such as visionary and strategic leadership, teamwork, empowerment and improved organizational culture which are integral to the NPM/Managerialist claims are value free; (2) contests and interrogates their universality of adoption and application; and (3) explores and examines the relevance and theoretical contributions of critical management studies (hereafter CMS) to NPM in particular and public management reform in general.